Green synthesis of gold nanoparticles using candida cylindracea culture supernatant - Noorbatcha, Ibrahim Ali; Zulkifli, Saifunnasr; Salleh, Mohd. Hamzah (2013)
The green synthesis of nanoparticles that have environmentally acceptable solvent systems and ecofriendly reducing agents is of great importance. Meanwhile, the synthesis of metal nanoparticles of different sizes, shapes, chemical composition and controlled monodispersity is a key area of research in nanotechnology because of their fascinating physical properties and technological applications. As such, biosynthesis of gold nanoparticles with small size and biostability is vital and used in various biomedical applications. In this paper we report the extracellular biosynthesis of gold nanoparticles (AuNPs) by using Candida cylindracea (also known as Candida rugosa), yeast. In the biosynthesis of AuNPs using this yeast, the cultured yeast was exposed to the chloroauric trihydrate. The bioreduction process involves Au+ ions which are reduced to metallic AuNPs through the catalytic effect of the extracellular enzyme. These gold nanoparticles were characterized by the means of UV–Vis spectroscopy, transmission electron microscopy (TEM), Xray Diffraction spectrum (XRD) and Fourier transform infrared spectroscopy (FTIR). UV–visible spectrum of the aqueous medium containing auric ion showed a peak at 530 nm corresponding to the surface plasmon resonance of gold nanoparticles. The intensity of the colour was found to be increases with respect of time. TEM micrograph showed the formation of well-dispersed gold nanoparticles in the range of 10–30 nm with spherical and triangular shape. Fourier transform infrared spectroscopy revealed possible involvement of reductive groups on the surfaces of nanoparticles. Hence the present study enlightens the green chemistry approach on the production of gold nanoparticles using a microorganism. In comparison to chemical synthesis, the synthesis of gold nanoparticles by microbial source is the most reliable method of production and yield.